Atraumatic Anterior Dislocation of the Hip Joint - Tadahiko Ohtsuru; Yasuyuki Morita; Yasuaki Murata; Junya Itou; Yuji Morita; Yutaro Munakata; Yoshiharu Kato (Case Reports in Orthopedics)
Dislocation of the hip joint in adults is usually caused by high-energy trauma such as road traffic accidents or falls from heights. Posterior dislocation is observed in most cases. However, atraumatic anterior dislocation of the hip joint is extremely rare. We present a case of atraumatic anterior dislocation of the hip joint that was induced by an activity of daily living. The possible causes of this dislocation were anterior capsule insufficiency due to developmental dysplasia of the hip, posterior pelvic tilt following thoracolumbar kyphosis due to vertebral fracture, and acetabular anterior coverage changes by postural factor. Acetabular anterior coverage changes in the sagittal plane were measured using a tomosynthesis imaging system. This system was useful for elucidation of the dislocation mechanism in the present case.